The role of oral dysbiosis in the development of oral diseases (LLC "Endo Press", 2020)
The analysis of influence of dysbiosis is conducted on development of diseases of oral cavity. The oral cavity is characterized by favorable conditions for breeding microflora due to slightly alkaline reaction of the environment, the availability of food residues, optimal humidity and temperature. Adverse factors such as functional disorders in the oral cavity, the changing nature of power, ecologically unfavorable living conditions, occupational hazards, the use of antimicrobial drugs contribute to the emergence of dysbiosis due to increase in total microbial contamination on a significant decrease in the proportion of obligate microflora, which creates prerequisites for the development of dental and even somatic pathology. The presence of oral dysbiosis causes the appearance of opportunistic infections, septic complications after maxillofacial trauma or surgery in the area, the development of stomatitis, periodontal disease, dental caries and its complications. It is proved that the qualitative and quantitative disorders symbiotic autochthonous microflora with subsequent development of any localization dysbiosis, a correction microbiocenosis.